1983
DOI: 10.1177/1077727x8301100308
|View full text |Cite
|
Sign up to set email alerts
|

Household Production of Food: Expenditures, Norms, And Satisfaction

Abstract: Pearson product moment correlations and multiple regression were used in this study to analyze the relationship between household production of food and the level of food expenditures; a household's assessment of the quantity and variety of food consumed; and a household's satisfaction with the quantity and variety of food consumed. Households that did more household production of food tended to have lower expenditures for food and to report their food to be of higher quantity and variety, when compared to a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
(6 reference statements)
2
8
0
Order By: Relevance
“…Household members who wish to adopt the strategy of substituting time, skills, and space for money will need to consider this when making housing decisions regarding location and tenure. The negative relationship found between primary household production of food and food expenditures in couple-headed households supports findings from a previous study (Volker et al, 1983).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Household members who wish to adopt the strategy of substituting time, skills, and space for money will need to consider this when making housing decisions regarding location and tenure. The negative relationship found between primary household production of food and food expenditures in couple-headed households supports findings from a previous study (Volker et al, 1983).…”
Section: Discussionsupporting
confidence: 90%
“…To assess the impact of primary household production of food on food expenditures and utility, factors associated with primary household food production activities need to be identified and controlled. With appropriate controls, any relationships found are true relationships, and not spurious (Rosenberg, 1968 . Studies of household production in general (and not just the primary production of food) have shown that higher levels of time spent in household production are associated with larger household sizes and younger children, while the amount of time in the labor force, particularly by the principal adult female in the household, has a negative relationship with household production (Goebel & Hennon, 1983;Nickols, 1976;Walker Woods, 1976). r~l®~ three studies (Kaitz, 1977; Morgan, Sirageidin, & ~aec°waldt, 1966;Volker et al, 1983) have focused on identifying family characteristics that predict participation in primary food production. Morgan et al examined five non-housework household production activities : 1) repairs, major housecleaning, and painting; 2) sewing; 3) providing their own food; 4) canning and freezing, and 5) all other activities that saved money.…”
Section: Primary Household Production Of Foodmentioning
confidence: 99%
See 3 more Smart Citations